ANALISIS PENCATATAN DAN PELAPORAN KEUANGAN UMKM - Syamsul, Syamsul (KEUNIS, 2022)
This study aims to describe the financial recording and reporting system of micro, small and medium enterprises (MSMEs). This population is 19,197 MSMEs and the research sample is 27 MSMEs in Palu City. Data were obtained through questionnaires and interviews with MSMEs. The data analysis technique used analysis descriptive. The results showed that the majority of MSMEs included in the micro-enterprise group had not recorded and reported financial statements. However, most of the small and medium-sized MSMEs have carried out financial recording and reporting both manually and computerized. Furthermore, most MSMEs have never attended financial management training, particularly financial recording and reporting. Therefore, MSMEs want training and assistance in financial recording and reporting by the government or other institutions. This information is important for the local government and related agencies in the context of counseling and mentoring business management in the future.